Re-Framing and Exploring Online Suicidal Games as a Specific Form of Cyberbullying - Thodelius, Charlotta (International Journal of Criminology and Sociology, 2022)
This article discusses online suicide games as a part of cyberbullying with the game called “Blue Whale Challenge” as an empirical case. The three-fold aim is to (i) identify key social mechanisms related to participation and engagement, (ii) discuss the phenomena in a broader sociological and criminological framework, and (iii) compare social mechanisms in BWC with mechanisms in cyberbullying. The analysis was conducted in two steps, firstly a case study based on a combination of media reports and extracts from different social media posts related to BWC was conducted. Secondly, the result from the case study was re-analyzed in relation to key elements identified in cyberbullying, to conclude if and how BWC can be defined as a form of cyberbullying. The results show that BWC can be defined as a specific form of cyberbullying, but victimization is created differently in BWC compared to victimization in cyberbullying.